Phosphite-containing adsorbents, systems including phosphite-containing adsorbents, and methods of using phosphite-containing adsorbents
By combining the adsorbent containing phosphite and the carrier material to form a CO2-efficient phase, the problems of high CO2 capture cost and poor stability of the adsorbent in the prior art are solved, and efficient and economical CO2 capture and stability are achieved.
Patent Information
- Application Number
- CN202380037952.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-05
- Filing Date
- 2023-04-04
- Publication Date
- 2024-12-13
AI Technical Summary
The existing CO2 capture technology is costly and the adsorbents have poor stability in the oxidative environment, which affects their service life and efficiency.
Using a phosphite-containing adsorbent, a CO2-binding molecule is combined with a phosphite-containing molecule to form a CO2-philic phase and combined it with a carrier material to form a porous structure to improve the stability of CO2 adsorption and release.
It reduces the cost of CO2 capture, extends the service life of the adsorbent, improves the adsorption efficiency and stability of CO2, and especially shows good antioxidant properties under an oxidative environment.
Smart Images

Figure CN119136907A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to co-pending U.S. provisional application No. 63 / 362,465, filed on April 5, 2022, entitled “Adsorbents, Systems Including Adsorbents, and Methods of Using Adsorbents,” the entire contents of which are incorporated herein by reference. Background Art
[0003] Greenhouse gases trap heat in the atmosphere, and carbon dioxide (CO2) is one of the main greenhouse gases. CO2 is emitted through human-related activities such as transportation, electricity, industry, and agriculture. In particular, CO2 emissions are caused by the burning of fossil fuels, solid waste, and trees, and through the manufacturing of cement and other materials. One way to reduce the amount of CO2 in the atmosphere is to capture CO2 using materials that have an affinity for CO2. Materials that can effectively capture CO2 are needed. Summary of the invention
[0004] The present disclosure provides phosphite-containing adsorbents (also referred to herein as "adsorbents" or "multiple adsorbents"), contactors, methods for capturing CO2 using adsorbents and contactors, structures including adsorbents, and systems and apparatus for capturing CO2 using adsorbents or contactors.
[0005] The present disclosure provides an adsorbent having a CO2-philic phase and a support, wherein the CO2-philic phase includes a CO2-binding molecule portion and a phosphite-containing molecule, and wherein the CO2-binding molecule includes a CO2-binding portion. The present disclosure provides a contactor including a structure and a structure adsorbent as described above and herein.
[0006] The present disclosure provides a system for capturing CO2 from a gas, optionally, the gas is ambient air, the system comprising: a first device configured to introduce gas into an adsorbent or contactor described above and herein to bind CO2 to the adsorbent; a second device configured to heat the adsorbent containing bound CO2 to at least a first temperature to release CO2; and a third device configured to collect the released CO2.
[0007] The present disclosure provides a method for capturing CO2 from a gas, optionally the gas is ambient air, the method comprising: introducing ambient air into an adsorbent or contactor as described above or herein to combine CO2 with the adsorbent; heating the adsorbent to at least a first temperature to controllably release CO2; and collecting CO2 in a CO2 collection device. The present disclosure provides a system for implementing the method described above and herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Other aspects of the present disclosure will be more readily understood when the detailed description of various embodiments of the present disclosure described below is read in conjunction with the accompanying drawings.
[0009] Figure 1A Schematic showing how the amine moiety binds CO2 to form a carbamate. Figure 1B The general mechanism of decomposition of peroxides by phosphites is shown. Figure 1C Schematic diagram of an adsorbent system consisting of a carrier and a CO2-philic phase. The carrier and the CO2-philic phase together constitute the adsorbent.
[0010] Figure 2 Schematic diagram of a honeycomb monolithic contactor consisting of a substrate and an adsorbent coating.
[0011] Figure 3 Shown are phosphite molecules evaluated as additives to polyethyleneimine (PEI).
[0012] Figure 4 The mass loss curve of the material when exposed to diluted air while increasing the temperature from room temperature to 900°C is shown.
[0013] Figure 5 Shown is the heat flow (DSC) curve of the material when it is exposed to diluted air while increasing the temperature from room temperature to 900°C.
[0014] Figure 6 The transient mass change curve of the TGA CO2 absorption experiment conducted at 400 ppm CO2 (DAC conditions) using the improved adsorbent containing PEI and phosphite additives supported in mesoporous alumina is shown.
[0015] 7A to 7D The degree of oxidation of PEI over time is shown as measured by differential scanning calorimetry (solid line, DSC) as described herein and in references, and by ( Fig. 7A )5%, ( Figure 7B )17% and ( Figure 7C ) The loss of amine efficiency at 30% O2 concentration (data point, AE) was measured; ( Fig.7D ) Oxidation degree of different PEI pore fillers. 7A to 7D Adapted from Nezam et al., ACS Sustainable Chem. Eng., 2021, Vol. 9, pp. 8477-8486.
[0016] Figure 8 Shown are transient oxidation curves of PEI and PEI containing a phosphite additive tested at 125°C in 20% CO2, 17% O2, balance N2.
[0017] Fig. 9 Shown are transient oxidation curves of PEI and PEI containing a phosphite additive tested at 137.5°C under 17% O2, balance N2.
[0018] Fig.10 Shown are the mass loss curve (dashed line) and heat flow (DSC, solid line) of a honeycomb monolith containing PEI and phosphite 5 when the temperature is raised to 900°C while exposed to dilute air. DETAILED DESCRIPTION
[0019] Embodiments of the present disclosure provide phosphite-containing adsorbents (also referred to herein as "adsorbents" or "adsorbents") and contactors, methods of using adsorbents and contactors to capture CO2, structures including adsorbents, and systems and apparatus for capturing CO2 using adsorbents and contactors. The methods, systems, and adsorbents of the present disclosure have advantages over current technologies because they are relatively more stable and reduce the cost of capturing CO2, particularly the cost of capturing CO2 from ambient air. In one aspect, the present disclosure provides an adsorbent having a carrier and a CO2-philic phase including molecules containing phosphite, thereby producing an adsorbent that effectively captures CO2.
[0020] Before describing the present disclosure in more detail, it should be understood that the present disclosure is not limited to the specific embodiments described, and as such may, of course, vary. It should also be understood that the terminology used herein is only used to describe specific embodiments and is not intended to be limiting, as the scope of the present disclosure is limited only by the appended claims.
[0021] Where a numerical range is provided, each intervening value (in units of one-tenth of the lower limit) between the upper and lower limits of the range and any other values or intervening values recited in the range is included in the scope of the present disclosure unless the context clearly dictates otherwise. The upper and lower limits of these smaller ranges may independently be included in the smaller ranges and are also included in the present disclosure, subject to any explicitly excluded limits in the range. When the range includes one or both limits, ranges excluding one or both of the limits are also included in the present disclosure.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present disclosure, preferred methods and materials are described herein.
[0023] It will be apparent to those skilled in the art after reading this disclosure that each individual embodiment described and illustrated herein has independent components and features that can be easily separated or combined with the features of any of the other multiple embodiments without departing from the scope or spirit of the disclosure. Any of the methods described can be performed in the order of events described or in any other order that is logically possible.
[0024]
[00136] Embodiments of the present disclosure will employ, unless otherwise indicated, techniques of chemistry, materials science, mechanical engineering, and the like, which are within the skill of the art.
[0025] The following examples are presented to provide those skilled in the art with a complete disclosure and description of how to implement the methods disclosed herein and use the probes disclosed and claimed herein. Efforts have been made to ensure the accuracy of numbers (such as amounts, temperatures, etc.), but some errors and deviations should be considered. Unless otherwise indicated, parts are by volume, temperatures are in ° C, and pressures are equal to or close to atmospheric pressure. Standard temperature and pressure are defined as 20 ° C and 1 atmosphere.
[0026] Before describing the embodiments of the present disclosure in detail, it should be understood that, unless otherwise stated, the present disclosure is not limited to specific materials, reagents, reaction materials, manufacturing processes, etc., as these may vary. It should also be understood that the terms used herein are only used to describe specific embodiments and are not intended to be limiting. In the present disclosure, steps may also be performed in different orders where logically possible.
[0027] It must be noted that throughout the specification and the appended claims, the singular forms ("a", "an", and "the") include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "compound" includes a plurality of compounds. Throughout this specification and the appended claims, reference will be made to a number of terms, which, unless a contrary intention is apparent, shall be defined as having the following meanings.
[0028] discuss
[0029] The present disclosure provides phosphite-containing adsorbents (also referred to herein as "adsorbents" or "adsorbents") and contactors, methods of using adsorbents and contactors to capture CO2, structures including adsorbents, and systems and apparatus for capturing CO2 using adsorbents and contactors. The present disclosure relates to various types of adsorbents and structures, which will be described below and herein.
[0030] In one aspect, the present disclosure provides an adsorbent and a contactor comprising a CO2-friendly phase and a carrier. The CO2-friendly phase comprises a CO2-binding molecule and a phosphite-containing molecule. The CO2-friendly phase can be a homogeneous mixture or a heterogeneous mixture. The CO2-binding molecule contains a CO2-binding portion. The ratio of the amount of the phosphite-containing molecule to the CO2-binding portion can be about 0.0001 mole to 1 mole, or about 0.1 mole to 1 mole of phosphite-containing molecules to 1 mole of CO2-binding portion, or about 0.01 mole to 0.5 mole or about 0.1 mole to 0.5 mole of phosphite-containing molecules to 1 mole of CO2-binding portion. When the CO2-binding molecule and the phosphite-containing molecule are mixed together, the phosphite-containing molecule can be used as a stabilizer for the CO2-binding molecule to improve its stability, thereby producing an improved CO2-friendly phase. In one aspect, when the improved CO2-friendly phase is incorporated into the pores of a porous carrier material, an effective CO2 adsorbent is formed, for example. Furthermore, sorbents made with the modified CO2-philic phase show less loss in their ability to capture CO2 after oxidative exposure compared to sorbents without the modification of the CO2-philic phase, thus enabling them to have a longer commercial lifetime.
[0031] A structured carrier, also called a shaped carrier or a structured carrier, refers to a carrier that has formed a structure, which is solid under standard conditions. The carrier can also be unstructured, which has a powdery texture under standard conditions. When referring to a carrier, if there is no mention of structure, formation or forming or structuring, it can refer to a structured or unstructured carrier.
[0032] The structured support may take the form of a homogeneous solid (ie, consisting essentially of the support but also containing components which render it stable under standard conditions) or as a coating on a substrate which is of a different composition than the coating and which provides mechanical stability to the coating.
[0033] In the process of removing CO2 from a gas stream (such as ambient air), it can be useful to use a structured support with a CO2-philic phase as a contactor. The contactor provides a geometry for the CO2-philic phase so that factors such as pressure drop, throughput and / or mass transfer rate can be optimized.
[0034] The CO2 binding molecule can be an amine or an amine polymer. The amine or amine polymer can include a primary amine, a secondary amine, a tertiary amine, or a mixture of any combination of primary amines, secondary amines and tertiary amines. The amine polymer can be branched, hyperbranched, dendritic or linear. The CO2 binding portion is an amine portion on the amine molecule or polymer. The amine portion interacts with CO2 to form a carbamate, carbonate or bicarbonate (. Figure 1A Schematic showing how the amine moiety binds CO2 to form a carbamate.
[0035] Primary amines are defined as having the chemical structure -NH2R 1 , where R 1 is an alkyl group, such as CH2 or CH3. A primary amine is defined as having the chemical structure -NHR 1 R 2 , where R 1 and R 2 are independently selected from alkyl groups, such as CH2 or CH3. Secondary amines are defined as having the chemical structure -NR 1 R 2 R 3 , where R 1 , R 2 and R 3 Independently selected from alkyl groups, such as CH2 or CH3.
[0036] The linear amine polymer can be defined as containing only primary amines, secondary amines, or both. The ratio of secondary amines to primary amines can be about 0.5 to 10,000. In one aspect, the molecular weight of the linear amine polymer can be about 100 g / mol to 100,000 g / mol, about 200 g / mol to 30,000 g / mol, or about 600 g / mol to 50,000 g / mol.
[0037] Branched amine polymers can be defined as containing any number of primary amines, secondary amines and tertiary amines that do not overlap with linear amine polymers or dendritic amine polymers. The ratio of primary amines, secondary amines and tertiary amines can be about 10:80:10 to 60:10:30, about 60:30:10 to 30:50:20 or about 45:45:10 to 35:45:20. It will be appreciated by those skilled in the art that the chemical structure of branched amine polymers can vary greatly and can be very complex. In one aspect, the molecular weight of branched amine polymers can be about 100 g / mol to 100000 g / mol, about 200 g / mol to 30000 g / mol or about 600 g / mol to 50000 g / mol.
[0038] Dendritic amine polymers can be defined as containing only primary and tertiary amines, wherein the groups of repeating units are arranged in a manner that is necessarily symmetrical in at least one plane through the center (core) of the molecule, wherein each polymer branch terminates with a primary amine, and wherein each branch point is a tertiary amine. The core or center connection is the same as the branched amine (e.g., ethyleneimine core and ethyleneimine branches, propyleneimine core and propyleneimine branches). The ratio of primary amine to tertiary amine can be about 1 to 3. In one aspect, the molecular weight of the dendritic amine polymer can be about 100 g / mol to 100000 g / mol, about 200 g / mol to 30000 g / mol, or about 280 g / mol to 3000 g / mol.
[0039] Hyperbranched amine polymers can be defined as having a chemical structure similar to that of dendritic amine polymers, but containing defects in the form of secondary amines (such as linear segments present in branched polymers), in this way providing a random chemical structure rather than a symmetric chemical structure. Hyperbranched amine polymers do not overlap with branched amine polymers or dendritic polymers. In the hyperbranched chemical structure, the ratio of primary amines, secondary amines and tertiary amines can be about 65:5:30 to 30:10:60. In one aspect, the molecular weight of the hyperbranched amine polymer can be about 100 g / mol to 100000 g / mol, about 200 g / mol to 30000 g / mol or about 600 g / mol to 10000 g / mol.
[0040] In one aspect, the linear amine polymers, hyperbranched amine polymers, and branched amine polymers contain secondary amines, while the dendritic amines do not, which can be advantageous because secondary amines bind strongly to CO2.
[0041] In one aspect, the amine polymer can be polyethyleneimine, polypropyleneimine, polyallylamine, polyvinylamine, polyglycidylamine, polystyrene-divinylbenzene polymer functionalized with amines (such as alkylbenzylamine moieties), or other amine polymers, each of which can be branched, hyperbranched, dendritic, or linear.
[0042] In one embodiment, the size (e.g., length, molecular weight), amount (e.g., number of different amine polymers) and / or type of the amine polymer can be selected based on the desired properties of the porous structure (e.g., carbon dioxide adsorption, regeneration properties, oxidative stability, loading, etc.).
[0043] In one aspect, the phosphite-containing molecule can play a role in removing hydrogen peroxide. In one aspect, the phosphite-containing molecule can be a substituted phosphite. In one aspect, although not limited by theory, as described below, the phosphite-containing molecule can be a substituted phosphite that removes hydrogen peroxide. In one aspect, the phosphite-containing molecule can be a substituted phosphite, such as a substituted phosphite can be a substituted aryl phosphite or a substituted phenyl phosphite. The phosphite can include one or a combination of the following substances: tris (2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, trimethyl phosphite, triethyl phosphite, diisooctyl phosphite, triheptanyl dipropylene glycol phosphite, triisodecyl phosphite, diphenyl isooctyl phosphite, diisooctyl phenyl phosphite, diphenyl tridecyl phosphite, triisooctyl phosphite, trilauryl phosphite, diphenyl phosphite, tri(dipropylene glycol) phosphite, dioleyl hydrogen phosphite phosphite), trilauryl trithio phosphite, bis(tridecyl) phosphite, tri(isodecyl) phosphite, tri(tridecyl) phosphite, diphenyldecyl phosphite, dinonylphenyl bis(nonylphenyl) phosphite, poly(dipropylene glycol) phenyl phosphite, tetraphenyl dipropylene glycol diphosphite, tri(nonylphenyl) phosphite, tri(2,4-di-tert-butylphenyl) phosphite, tri(2,4-di-tert-butyl-5-methylphenyl) phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl] phosphite, tri(decyl) phosphite, octyl diphenyl phosphite, di(decyl) monophenyl phosphite, alkyl(C10) bisphenol A phosphite Acid, tetraphenyl-tetra(tridecyl) pentaerythritol tetrasulfite, bis(2,4-di-tert-butyl-6-methylphenyl) ethyl phosphite, tetra(tridecyl) isopropylidene diphenol diphosphite, tetra(tridecyl)-4,4'-n-butylene bis(2-tert-butyl-5-methylphenol) diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl) butane triphosphite, tetra(2,4-di-tert-butylphenyl) biphenyl diphosphite, 9,10-dihydro-9-oxa-10-phosphophanate-10-oxide, (1-methyl-1-propenyl-3-ylidene) tris(1,1-dimethylethyl)-5-methyl-4,1-phenylene) hexanoic acid phosphite (hexato Ridecylphosphite), 2,2'-methylenebis(4,6-di-tert-butylphenyl)-2-ethylhexyl phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)-octadecyl phosphite, 2,2'-ethylenebis(4,6-di-tert-butylphenyl)fluorophosphite, 4,4'-butylenebis(3-methyl-6-tert-butylphenylbis(tridecyl))phosphite, tris(2-[(2,4,8,10-Tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphin-6-yl)oxy]ethyl)amine, 3,9-bis(4-nonylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphospiro[5,5]undecane, 2,4,6-tri-tert-butylphenyl-2-butyl-2-ethyl-1,3-propanediol phosphite, poly-4,4'-isopropylidene diphenol C12-15 alcohol phosphite, bis(diisodecyl)pentaerythritol Diphosphites, bis(tridecyl) pentaerythritol diphosphite, bis(octadecyl) pentaerythritol diphosphite, bis(nonylphenyl) pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,4,6-tri-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, bis(2,4-dicumylphenyl) pentaerythritol diphosphite, etc.
[0044] While not intending to be bound by theory, the addition of phosphite-containing molecules to the CO2-philic phase can modulate the properties of the CO2-philic phase. The amount, type, and mixture of phosphite molecules can be adjusted and varied to achieve the desired properties of the CO2-philic phase. There are a variety of phosphites sold on the market as antioxidants, such as tris(2,4-di-tert-butylphenyl)phosphite (trade name Irgafos 168) and tris(nonylphenyl)phosphite. For example, phosphites are secondary antioxidants that decompose peroxides into stable non-radical products. When used in combination with primary antioxidants, they are very effective stabilizers. Trivalent phosphorus compounds reduce hydroperoxides to alcohols and themselves convert to phosphates. The general mechanism of decomposition of peroxides and phosphites is as follows Figure 1B shown.
[0045] In one aspect, it is highly advantageous to increase the stability of the CO2-philic phase under process conditions relevant to the use of the adsorbent in CO2 separation processes, particularly during adsorbent regeneration (a process cycle in which the adsorbent temperature is increased to remove bound CO2). It is also advantageous to increase the stability of the CO2-philic phase under conditions relevant to the storage of the adsorbent when the adsorbent is not in use in a process or plant. It is valuable to have an adsorbent containing a CO2-philic phase with improved stability under process conditions involving adsorbent regeneration, storage, or both adsorbent regeneration and storage.
[0046] It is useful to evaluate the oxidative stability of a material in an environment containing both oxygen and CO2 because during the regeneration process, the desorbed CO2 will be present in different concentrations and, combined with the oxygen at elevated temperatures, will affect the stability of the material. Alternatively, evaluating the oxidative stability of a material with oxygen (air) alone is a useful method for assessing the shelf life of a material when stored under ambient conditions.
[0047] As mentioned above, CO2-friendly phase (for example, the homogeneous or heterogeneous combination of the molecule containing phosphite and CO2 binding molecule) can be homogeneous or heterogeneous.When CO2-friendly phase is heterogeneous, the molecule containing phosphite and CO2 binding molecule can exist in a variety of ways.For example, the molecule containing phosphite and CO2 binding molecule can be mixed, then applied or mixed in the structure.In another example, the molecule containing phosphite and CO2 binding molecule can be applied or mixed separately, but once applied or mixed, the molecule containing phosphite and CO2 binding molecule have just formed CO2-friendly phase.In one aspect, the molecule containing phosphite and CO2 binding molecule can be applied or mixed separately, to form CO2-friendly phase layer on a carrier (for example, on the pore surface of a carrier). In another aspect, the mixture of phosphite-containing molecules and CO2 binding molecules can be coated on a carrier to form a layer (for example, on the pore surface of the carrier), and optionally the molecules containing phosphite and CO2 binding molecules can be coated or incorporated into the layer (for example, on the pore surface of the carrier) on the carrier respectively. In another aspect, independently of or in combination with, for example, other aspects mentioned above, the one containing phosphite molecules and CO2 binding molecules can be used to form part of the carrier or all of the carrier, wherein the function of the parent CO2 phase is as described herein. Various combinations can be considered and are also a part of the present disclosure. Other homogeneous and / or heterogeneous methods of applying, using or incorporating parent CO2 phases are also described herein and below.
[0048] As described herein, the adsorbent includes a CO2-philic phase (e.g., a homogeneous or heterogeneous combination of molecules containing phosphite and CO2-binding molecules) and a support. The support includes a surface (e.g., a surface that can be exposed to a CO2-containing gas and / or can interact with the CO2-philic phase during conventional use). The surface can be a pore surface and / or other surface that contacts or interacts with the CO2-philic phase.
[0049] In one aspect, the CO2-philic phase (e.g., a homogeneous or heterogeneous combination containing phosphite molecules and CO2-bound molecules) can be disposed on or in a carrier to form an adsorbent. The CO2-philic phase can be disposed on the surface of the carrier and / or in the pores of the carrier, and / or on the outer surface of the carrier or any combination thereof. In one aspect, the CO2-philic phase can be a coating on a porous material surface, a monolayer on a porous material surface, a self-assembled monolayer on a porous material surface, a bulk phase in a porous material pore, a coating on a porous material outer surface, etc.
[0050] In one aspect, the support can be made of one or more types of materials, such as ceramics, metals, metal oxides, plastics, cellulose, carbon, zeolites, metal organic frameworks (MOFs), porous organic frameworks (POFs), covalent organic frameworks (COFs), intrinsically microporous polymers (PIMs), polymers, fibrous cellulose, glass fibers, or boron nitride fibers, etc. In another aspect, the support can also be made of a material that includes a CO2-philic phase.
[0051] The metal oxide support can be selected from: cordierite, alumina (e.g., γ-alumina, θ-alumina, δ-alumina), cordierite-α-alumina, silica, aluminum silicate, zirconium oxide, germanium oxide, magnesium oxide, titanium dioxide, hafnium dioxide, silicon nitride, zirconium mullite, spodumene, alumina-silica-magnesium oxide, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite and combinations thereof. In the case where the oxide contains formal charges, the charges can be balanced by appropriate counterions, such as cations of NR4, Na, K, Ca, Mg, Li, H, Rb, Sr, Ba, Cs or anions including phosphate, phosphite, sulfate, sulfate, nitrate, nitrite, chloride, bromide, etc. The metal oxide can contain dopants, such as zirconium, iron, tin, silicon, titanium, magnesium and combinations thereof. It is well known that the surface of the metal oxide can contain acidic, basic and neutral sites, and dopants can change the number and strength of surface acidic and basic sites.
[0052] In one aspect, the polymer carrier can be a polymer and / or copolymer of a polyolefin, a polyester, a polyurethane, a polycarbonate, a polyetheretherketone, a polyphenylene oxide, a polyethersulfone, a melamine, a polyamide, a polyvinylbenzene, a polystyrene-divinylbenzene, a polyurethane, a polyacrylate, a polystyrenes, a polyacrylonitrile, a polyimide, a polyfurfuryl alcohol, a phenolfurfuryl alcohol, a melamine formaldehyde, a resorcinol formaldehyde, a cresol formaldehyde, a phenol formaldehyde, a polyvinyl alcohol dialdehyde, a polycyanurate, a polyacrylamide, various epoxy resins, agar and agarose, or a combination thereof.
[0053] The carrier can be porous (e.g., macroporous, mesoporous, microporous, or a mixture thereof (e.g., a macroporous surface can include mesopores and / or micropores within one or more macropores, wherein the mesoporous surface can include micropores, etc.)). In one aspect, the porous structure is mesoporous. The pores can extend through the porous structure or the porous layer, or only extend to a certain depth. The macropores of the porous structure can have a diameter of about 100nm to 10000nm, a length of about 500nm to 100000nm, and a volume of 0.2cc / g to 1cc / g. The mesopores of the porous structure can have a diameter of about 5nm to 100nm, a length of about 10nm to 10000nm, and a volume of 0.1cc / g to 2cc / g. The micropores of the porous structure can have a diameter of about 0.5nm to 5nm, a length of about 0.5nm to 1000nm, and a volume of about 0.1cc / g to 1cc / g.
[0054] The support may be porous and have a porosity of at least 90%, at least 85%, at least 80%, at least 75%, at least 70%, at least 65%, at least 60%, or about 60% to 90%. In some embodiments, the surface area of the support may be 1 m 2 / g or more, 10m 2 / g or more, 100m 2 / g or more, 150m 2 / g or more, 200m 2 / g or more, 250m 2 / g or more, 500m 2 / g or more, 1000m 2 / g or greater.
[0055] In an embodiment, the CO2-philic phase (e.g., a homogeneous or heterogeneous combination of molecules containing phosphite and CO2-binding molecules) can be physically impregnated in the internal volume pores of the porous structure without being covalently bonded to the inner surface of the pores of the porous structure, can be grafted (e.g., directly or indirectly covalently bonded) to the inner surface of the pores of the porous structure, or a combination thereof. In an embodiment, the CO2-philic phase (e.g., a homogeneous or heterogeneous combination of molecules containing phosphite and CO2-binding molecules) can be covalently bonded (e.g., directly bonded to the surface or bonded through a connecting group) to the surface of a material, the surface of which may include a porous layer or the inner surface of the pores of the porous structure. In one aspect, covalent bonding can be achieved using techniques known in the art for bonding adsorbents. With respect to the CO2-philic phase (e.g., a homogeneous or heterogeneous combination of molecules containing phosphite and CO2-binding molecules) being physically impregnated in the pores of the porous structure and not covalently bonded to the inner surface of the pores of the porous structure, the CO2-philic phase can be confined within the pores of the carrier, but not bonded to the surface. In another embodiment, the CO2-philic phase (e.g., a homogeneous or heterogeneous combination of phosphite-containing molecules and CO2-binding molecules) is present in a plurality of pores (internal volume) of a porous structure (a "porous structure" may include a structure having pores on its surface or a structure having a porous layer or coating on the surface of the structure (wherein the structure itself may or may not be porous)), wherein the loading amount of the CO2-philic phase is about 10 wt % to 75 wt % of the support. With respect to the loading amount, it is determined by thermogravimetric analysis (TGA).
[0056] In some embodiments, the carrier may include a surface layer located on the pore surface of the carrier that can be combined with the CO2-philic phase. In one aspect, the surface layer may include an organic modified portion (e.g., alkyl, amine, thiol, phosphine, etc.) on the surface of the material (e.g., the outer surface and / or inner surface of the pore). In an embodiment, the surface layer may include surface alkyl, amine, thiol, phosphine, etc., and the CO2-philic phase may be directly covalently bonded and / or indirectly covalently bonded (e.g., covalently bonded to a linker covalently bonded to the material). In an embodiment, the surface layer may include an organic polymer having one or more of the following groups: alkyl, amine, thiol, phosphine, etc. In another embodiment, the structure may include a carbon carrier, wherein the carbon carrier may include one or more of the following groups: alkyl, amine, thiol, phosphine, etc.
[0057] In embodiments, the CO2-philic phase may occupy about 10% to 100% of the mesoporous volume of the support, or may occupy about 30% to 90% of the mesoporous volume of the support, or may occupy about 40% to 80% of the mesoporous volume of the support, or may occupy about 50% to 70% of the mesoporous volume of the support.
[0058] The methods of making the shaped supports or structures described above and herein can be used to create any of the structures listed in this paragraph and the following paragraphs. An adsorbent comprising a CO2-philic phase and a support can form a structure or be applied to a structure. In one aspect, the CO2-philic phase and the support can form 100% or less than 100% of the structure (e.g., ranging from about 10%, about 20%, about 30%, about 40%, about 50% and about 60%, about 70%, about 80%, about 90%, about 99% of each combination, such as about 10% to 99%, about 10% to 80%, about 10% to 50%, about 50% to 99%, about 50% to 90%, about 50% to 80%), wherein there is a sufficient amount of adsorbent on the surface of the structure to absorb the required amount of CO2. In one aspect, the structure can be a honeycomb, a laminate, a foam, a fiber, a minimal surface solid, a powder disc, a granule, a powder, etc., or a combination of two or more of the above.
[0059] In one aspect, the structure can be porous and have a porosity of at least 90%, at least 85%, at least 80%, at least 75%, at least 70%, at least 65%, at least 60%, or about 60% to 90%.
[0060] In one aspect, the porosity of the structure can be composed of macropores, mesopores and / or micropores. In one aspect, the CO2-philic phase is mainly (e.g., about 40% to 100% or about 50% to 90% or about 60% to 80%) located in the mesopores of the structure.
[0061] In one aspect, the structure can be composed entirely of the adsorbent, or include other substrate materials such as ceramics, metals, metal oxides, plastics, or other materials. The structure can be a porous substrate, or can include a partial or complete porous coating on a porous substrate, wherein the CO2-philic phase can be present in the pores of one or both of the porous substrate and the porous coating.
[0062] When the structure is composed entirely of an adsorbent (e.g., a homogeneous or heterogeneous combination of phosphite molecules and CO2 binding molecules and a carrier), it can be formed by methods such as extrusion, molding, 3D printing, etc. The structure can be formed using a carrier material that does not contain a CO2-philic phase or using a carrier that has been incorporated with a CO2-philic phase. When formed without a CO2-philic phase, the CO2-philic phase can be incorporated into the structure by impregnation, grafting, or other functionalization techniques.
[0063] In a specific aspect, the support material can be applied to the substrate surface as a porous coating (also referred to as a "support coating"). In one embodiment, the porous coating can be a foam, such as a polymer foam (e.g., polyurethane foam, polypropylene foam, polyester foam, etc.), a metal foam, or a ceramic foam. The porous coating can include a metal oxide layer (e.g., a foamed metal oxide layer). For example, the metal oxide layer can be silicon dioxide or aluminum oxide on the surface of the substrate. The porous coating can be present on the surface of the substrate, in the pores or voids of the substrate, or in a combination thereof. The thickness of the porous coating can be about 50 μm to 1500 μm, and the pores can have the sizes described above and herein.
[0064] In one aspect, the support material, substrate and / or structure can be made of a ceramic substrate such as cordierite, alumina (e.g., γ-alumina, θ-alumina, δ-alumina), cordierite-α-alumina, silica, aluminum silicate, zirconium oxide, germanium oxide, magnesium oxide, titanium dioxide, hafnium dioxide, silicon nitride, zirconium mullite, spodumene, alumina-silica-magnesium oxide, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite and combinations thereof. The metal or metal oxide structure can be aluminum, titanium, stainless steel, Fe-Cr alloy or Cr-Al-Fe alloy. In the case where the oxide contains formal charges, the charges can be balanced by appropriate counterions, such as cations of NR4, Na, K, Ca, Mg, Li, H, Rb, Sr, Ba, Cs or anions including phosphate, phosphite, sulfate, sulfate, nitrate, nitrite, chloride, bromide, etc.
[0065] In one aspect, the support material, substrate and / or structure can be made of a plastic substrate, which can be made of a polymer and / or copolymer of polyolefins, polyesters, polyurethanes, polycarbonates, polyetheretherketones, polyphenylene oxides, polyethersulfones, melamines, polyamides, polyvinylbenzenes, polystyrene-divinylbenzene, polyurethanes, polyacrylates, polystyrenes, polyacrylonitrile, polyimides, polyfurfuryl alcohol, phenolfurfuryl alcohol, melamine formaldehyde, resorcinol formaldehyde, cresol formaldehyde, phenol formaldehyde, polyvinyl alcohol dialdehyde, polycyanurate, polyacrylamide, various epoxy resins, agar and agarose, or combinations thereof.
[0066] In one embodiment, the structure can be a honeycomb structure, such as a honeycomb monolithic structure including a channel. The honeycomb structure can have a regular corrugated structure. The length and width of the honeycomb monolithic structure can be in the order of centimeters to meters, while the thickness can be in the order of millimeters to centimeters or more. In one aspect, the honeycomb monolithic structure does not have a fiber size. In other words, the honeycomb structure can be a flow-through substrate comprising an open channel defined by a channel wall. There can be about 50 to about 900 cells per square inch of channel. The cross section of the channel can be polygonal (e.g., square, triangular, hexagonal, octagonal), sinusoidal, circular, etc. Along the length of the channel, the channel can have a straight, zigzag, inclined or herringbone shape. The length of the channel can be 1 mm to tens of centimeters or hundreds of centimeters or longer. The channel can have perforated or shuttered walls. In one aspect, the adsorbent can be disposed in the pores of the honeycomb structure and / or in the pores of the porous layer on the surface of the honeycomb structure. The honeycomb structure may have a geometric void fraction (also referred to as open area) of 0.3 to 0.95 or about 0.5 to 0.9.
[0067] In embodiments, the honeycomb structure may include an inlet end, an outlet end, and internal channels extending from the inlet end to the outlet end. In some embodiments, the honeycomb structure includes a plurality of cells extending from the inlet end to the outlet end, the cells being defined by intersecting cell walls or channel walls.
[0068] In one aspect, the honeycomb structure and / or substrate may be a ceramic (e.g., Corning Inc., marketed under the trademark The adsorbent may be coated or otherwise fixed within the pores of the ceramic honeycomb structure and / or within a porous layer on the surface of the ceramic honeycomb structure. In one aspect, the porous coating may include a layer of a metal oxide (such as silicon dioxide or aluminum oxide) on the surface of the substrate. In one embodiment, the metal oxide layer may be mesoporous and macroporous. The depth of the honeycomb as a whole may be from 3 inches to 10 feet or from about 3 inches to 24 inches.
[0069] In one aspect, the structure can be a laminate. A laminate is a structure comprising a one-dimensional wall structure in which sheets are stacked together with spaces between each sheet so that gas can flow between the sheets.
[0070] In one aspect, the structure can be a foam. A foam is a structure of irregular channel structures surrounded by irregular solid structures. The solid structures are interconnected so that the foam material is self-standing.
[0071] In one aspect, the structure can be a plurality of fibers. A fiber is a structure having a high aspect ratio that can be arranged in a regular array relative to one another when supported at least at one end of the fiber in a gas contacting application. The fiber can be solid or hollow.
[0072] In one aspect, the structure can be a minimum surface solid. Minimum surface solids are commonly used structures in distillation and absorption systems to increase the contact area with materials and fluids. Minimum surface solids refer to geometric shapes with an average surface area of zero, including shapes such as helical surfaces. For example, the helical surface can be a sinusoidal shape.
[0073] In one aspect, the structure can be a powder tray. A powder tray structure is one in which a tray holds loose powder or particles of the adsorbent of the present disclosure to form a structured contactor without the material itself forming a self-supporting structure. Powder trays can be arranged in stacked layers to form sheets, thereby forming a structure similar to a laminate. These layers can be created using flexible sheets, rigid sheets, or other flat surfaces mounted on a rigid frame structure. Powders are loose, free-flowing solids with a small characteristic particle size to provide a powdery consistency. Particles are beads, spheres, or other compacted structures used to provide structure and surface area for the adsorbent.
[0074] In one aspect, the structure can be a sorbent particle volume. The sorbent particle volume can be surrounded by one or more walls so that gas can pass through the walls while keeping the sorbent inside. The sorbent particle volume can be arranged relative to other sorbent particles, for example to approximate a honeycomb, fiber, or other structured contactor having a body.
[0075] In one aspect, adsorbents in the form of contactors (e.g., structures) are effective embodiments of an efficient method for capturing CO2 from ambient air or other gas mixtures (e.g., flue gas, exhaust gas, natural gas, or other gases containing CO2) because the structured contactor or contactors can be designed to provide high surface area and low pressure drop for air treatment. The contactor can be in the form of honeycombs, laminates, foams, fibers, minimum surface solids, powder discs, granules, powders, etc., or a combination of two or more of the above.
[0076] Now that embodiments of the adsorbent and structure have been described, additional details about the systems and methods of the present disclosure are provided. The present disclosure provides a method for capturing CO2 from ambient air or other gas mixtures (e.g., flue gas, exhaust gas, natural gas, or other gas containing CO2). The method includes introducing ambient air into an adsorbent (e.g., a structure), heating the adsorbent (e.g., about 10°C to 200°C higher than the conventional adsorbent temperature to absorb CO2) to at least a first temperature to controllably release CO2; and collecting CO2 in a CO2 collection device. The temperature of the adsorbent can be increased by contacting the adsorbent with a gas at high temperature, contacting the adsorbent with a fluid at high temperature, contacting the absorbent with a heat exchanger through which a hot fluid or gas flows, heating the walls of a container, vessel, or other sealed device containing the adsorbent, or contacting the adsorbent with steam (e.g., the temperature of the steam can be 60°C to 200°C and is saturated or superheated). In one aspect, the method can be implemented using the system described below.
[0077] The present disclosure provides a system and apparatus for capturing CO2 from ambient air or other gas mixtures (e.g., flue gas, exhaust gas, natural gas or other gases containing CO2), wherein the removal of CO2 is important. Typically, the system includes a first device, which is configured to introduce ambient air or other gas mixtures into an adsorbent or contactor, wherein the adsorbent or contactor includes those described herein. The adsorbent is exposed to ambient air or other gas mixtures for a period of time (e.g., several hours). In a specific aspect, the adsorbent is a honeycomb integral body with an opening area of 0.3 to 0.95. For example, the first device is configured to deliver ambient air to the honeycomb integral body at a speed between 0.25m / s and 10m / s. After the desired time, the second device is configured to heat the adsorbent containing the combined CO2 to at least a first temperature (e.g., about 40°C to 200°C, about 50°C to 200°C or about 60°C to 200°C) to release CO2. The second device of the system can be operated to desorb CO2 by an adsorbent. The second device may include components that support temperature fluctuations, pressure fluctuations, steam fluctuations, concentration fluctuations, combinations thereof, or other dynamic processes to desorb CO2. In an embodiment, the steam fluctuation process may include exposing the adsorbent to steam, wherein the temperature of the steam is about 60°C to 150°C and the absolute pressure of the steam is about 0.2 bar to 5 bar. The third device is configured to collect the released CO2. The system may be operated to allow the adsorbent to absorb and desorb CO2 in an efficient and economical manner.
[0078] Various aspects of the invention can be described in the following paragraphs.
[0079] The present disclosure provides an adsorbent comprising a CO2-philic phase and a carrier, wherein the CO2-philic phase comprises a CO2-binding molecule portion and a phosphite-containing molecule, wherein the CO2-binding molecule comprises a CO2-binding portion. The CO2-philic phase is an amine. The amine is an amine polymer. The amine polymer can be branched, hyperbranched, dendritic or linear. The amine polymer is one of the following substances: polyethyleneimine, polypropyleneimine, polyallylamine, polyvinylamine, polyglycidylamine, or a polystyrene-divinylbenzene polymer functionalized with an amine or other amine polymer. The phosphite-containing molecule is a substituted phosphite, and optionally, the substituted phosphite is a substituted aryl phosphite or a substituted phenyl phosphite. The phosphite-containing molecule is selected from: tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, trimethyl phosphite, triethyl phosphite, diphenyl phosphite, tridodecyl trithiophosphite, trinonylphenyl phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. The amine is physically impregnated into the pores of the support. The amine is physically impregnated onto the surface of the support. The amine is covalently bonded to the surface of the support. The support is a ceramic, a metal, a metal oxide, a plastic, a cellulose, a carbon, a zeolite, a metal organic framework (MOF), a porous organic framework (POF), a covalent organic framework (COF), an intrinsic microporous polymer (PIM), a polymer, a fibrous cellulose, a glass fiber, or a boron nitride fiber.
[0080] The present disclosure provides a contactor, which includes a structure or adsorbent as described above or herein. The structure is selected from honeycomb, laminate, foam, fiber, minimum surface solid, powder disk, particle or structure and combination thereof.
[0081] The present invention provides a system for capturing CO2 from a gas, optionally the gas is ambient air, the system comprising: a first device configured to introduce a gas into an adsorbent or contactor as described above and herein to bind CO2 to the adsorbent; a second device configured to heat the adsorbent containing bound CO2 to at least a first temperature to release CO2; and a third device configured to collect the released CO2. The adsorbent is regenerated after heating so that it can absorb CO2 from the gas. The adsorbent can be in the form of a honeycomb, a laminate, a fiber, a foam, a granule, a powder disc, or a combination thereof. The open area of the honeycomb is 0.3 to 0.95. The gas approaches the honeycomb at a speed of 0.25 m / s to 10 m / s. The system is configured to operate to remove CO2 from ambient air, wherein the ambient air has a low concentration of CO2.
[0082] The present disclosure provides a method for capturing CO2 from a gas, optionally the gas is ambient air, the method comprising: introducing ambient air into an adsorbent or contactor as described above or herein to combine CO2 with the adsorbent; heating the adsorbent to at least a first temperature to controllably release CO2; and collecting CO2 in a CO2 collection device. Heating the adsorbent regenerates the adsorbent, enabling it to absorb CO2 from ambient air. The adsorbent is heated by contact with steam. The method is configured to operate to remove CO2 from ambient air, wherein the ambient air has a low concentration of CO2. The adsorbent is in the form of a honeycomb, a laminate, a fiber, a foam, a granule, a powder disc, or a combination thereof.
[0083] The present disclosure provides a system for implementing the method as described above and herein.
[0084] Example
[0085] Now that embodiments of the present disclosure have been described, generally, Example 1 describes some other embodiments of the present disclosure. Although embodiments of the present disclosure are described in conjunction with Example 1 and the corresponding text and drawings, it is not intended to limit the various embodiments of the present disclosure to these descriptions. On the contrary, the intention is to cover all alternatives, modifications, and equivalents included in the spirit and scope of the embodiments of the present disclosure.
[0086] Example 1
[0087] Removing CO2 from ambient air through engineered chemical processes, also known as direct air capture (DAC), is becoming an important environmental technology for mitigating climate change. DAC is a technology that can provide negative emissions and remove CO2 from the atmosphere. However, current DAC technology is expensive, which limits its deployment. Therefore, there is a need to improve DAC technology. Many DAC technologies rely on solid adsorbent materials as a medium for separating CO2 from the air. These adsorbents are typically applied in a temperature swing process, where at low temperatures, CO2 in the air binds to sites in the adsorbent, and then at high temperatures the CO2 is released into a concentrated product that can be sequestered or sold as a product. Many DAC adsorbents utilize amines to bind CO2 in this way. Some amines can effectively bind low concentrations of CO2, such as CO2 in air (400ppm).
[0088] While certain amines are effective at binding CO2 from ambient air, they slowly oxidize in ambient oxygen. This effect is exacerbated during process cycles where the sorbent temperature is increased to remove the bound CO2, thereby accelerating oxidative degradation and shortening the useful life of the CO2 sorbent. Therefore, there is a need for sorbents with improved oxidative stability for effective removal of CO2 from ambient air.
[0089] Some adsorbents used in the DAC process are composite materials containing a CO2-philic phase (e.g., a CO2-binding molecule and a phosphite-containing molecule) that is distributed in or inside a solid material that provides it with a surface area. The CO2-philic phase can be grafted onto a solid surface, physically impregnated into the pores of a solid material, or physically supported on the surface of a solid material. The CO2-philic phase of these adsorbents can be an amine or other molecule that can bind to CO2. In some cases, the amine can be a polymeric amine, such as polyethyleneimine, polypropyleneimine, polyallylamine, polyethyleneamine, polybutylamine, or other amines. These polymeric amines can be linear, branched, hyperbranched, dendritic, or other forms of macromolecules. In other cases, the amine can be a small molecule, such as TEPA, TPTA, or others. In other cases, the amine can be an aminosilane. The solid support material can be a metal oxide, carbon, metal, or other structure that can provide sufficient surface area for the deposition of the CO2-philic phase, thereby achieving useful CO2 adsorption and desorption capacity and kinetics. In this way, the solid support material is functionalized with the CO2-philic phase to form a composite adsorbent.
[0090] The adsorbent may be formed or incorporated into a macrostructure or contactor to provide advantages in applications such as DAC. Such structures may be honeycomb monoliths, laminates, particles, or other structures that provide a high geometric surface area for air or CO2-containing gas to effectively contact the adsorbent so that the CO2 can bind to the adsorbent.
[0091] Adsorbents can be used in processes to capture CO2 from air or various other gas streams (such as flue gas, natural gas, etc.). These processes are called "CO2 capture processes". CO2 capture processes can use temperature fluctuations, concentration fluctuations, pressure fluctuations, steam stripping or other fluctuation techniques to remove CO2 bound to the adsorbent surface.
[0092] There is relatively little development of CO2 adsorbents improved by polyethyleneimine, especially for DAC applications.
[0093] Having now described embodiments of the present disclosure, in general, the following examples describe some other embodiments of the present disclosure. Although embodiments of the present disclosure are described in conjunction with these examples and corresponding text and drawings, it is not intended to limit the various embodiments of the present disclosure to these descriptions. On the contrary, the purpose is to cover all alternatives, modifications and equivalents included in the spirit and scope of the embodiments of the present disclosure.
[0094] Figure 1C Schematic diagram of an adsorbent system consisting of a carrier and a CO2-philic phase. The carrier and the CO2-philic phase together constitute the adsorbent. Figure 1CThe main components of the adsorbent system are shown. The adsorbent system consists of a support material and a CO2-philic phase. In the schematic diagram shown, a single CO2-philic phase is incorporated into a single support. The CO2-philic phase shown is polyethyleneimine (PEI). One of the known CO2 and PEI adsorption products is ammonium carbamate. Mesoporous alumina is shown as a support.
[0095] Figure 2 Schematic diagram of a honeycomb monolithic structure consisting of a substrate and an adsorbent washcoat. The adsorbent washcoat consists of a support material and a CO2-philic phase. This example shows a cordierite substrate, an alumina support, and a PEI CO2-philic phase.
[0096] Figure 2 An embodiment of a honeycomb monolith contactor is shown. The figure shows the main geometric features of the honeycomb monolith, which has straight flow channels surrounded by walls. The figure schematically shows a washcoat coated on the wall, wherein the washcoat is composed of an adsorbent. The adsorbent is composed of a support material and a CO2-philic phase (e.g., PEI).
[0097] Exemplary phosphite molecules are Figure 3 shown.
[0098] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and 9,10-Dihydro-9-Oxa-10-Phosphaphenanthrene-10-Oxide
[0099] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used was 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (CAS No. 35948-25-5), which was obtained from Fisher Scientific and is a commercially available antioxidant containing a non-aromatic phosphite ring and two aromatic substituents. PEI was dissolved in a methanol solution, and then phosphite was added in a ratio of 0.1 mol of phosphite per mol of N present in PEI and stirred until uniform. Then, mesoporous alumina was dispersed in the mixture. After stirring for >4h, the solvent was removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite was controlled so that the PEI / phosphite mixture filled about 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent had a powdery texture.
[0100] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and Tridodecyl Trithiophosphite
[0101] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used is tri(dodecyl) trithiophosphite (CAS No.: 1656-63-9), which is from Fisher Scientific and is a commercially available phosphite containing aliphatic sulfides. PEI is dissolved in a methanol solution, and then the phosphite is added in a ratio of 0.1 mol of phosphite per mol of N present in PEI. The solution is then mixed and stirred until uniform. Then, mesoporous alumina is dispersed in the mixture. After stirring for>4h, the solvent is removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite is controlled so that the PEI / phosphite mixture fills 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent has a powdery texture.
[0102] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and Diphenyl Phosphite
[0103] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used is diphenyl phosphite (CAS number: 4712-55-4), which comes from Fisher Scientific and is a commercially available diorganophosphite. The phosphite is tetrahedral and contains two phenols. PEI is dissolved in a methanol solution, and then the phosphite is added in a ratio of 0.1 mol of phosphite per mol of N present in PEI, and stirred until uniform. Then, mesoporous alumina is dispersed in the mixture. After stirring>4h, the solvent is removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite is controlled so that the PEI / phosphite mixture fills 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent has a powdery texture.
[0104] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and Tris(nonylphenyl)phosphite
[0105] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used is tris(nonylphenyl)phosphite (CAS No.: 26523-78-4) and is a commercially available antioxidant. This phosphite contains three substituted phenols with aliphatic groups. PEI was dissolved in a methanol solution, and then the phosphite was added in a ratio of 0.1 mol of phosphite per mol of N present in PEI and stirred until uniform. Then, mesoporous alumina was dispersed in the mixture. After stirring for >4h, the solvent was removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite was controlled so that the PEI / phosphite mixture filled 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent had a powdery texture.
[0106] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and Tris(2,4-di-tert-butylphenyl) Phosphite
[0107] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used is tris(2,4-di-tert-butylphenyl) phosphite (CAS No.: 31570-04-4) and is a commercially available organic phosphite stabilizer with the trade name Irgafos168. This phosphite contains three substituted phenols with tert-butyl groups. PEI was dissolved in a methanol solution and then the phosphite was added in a ratio of 0.1 mol of phosphite per mol of N present in PEI. The solution was then mixed and stirred until uniform. Then, mesoporous alumina was dispersed in the mixture. After stirring for >4h, the solvent was removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite was controlled so that the PEI / phosphite mixture filled 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent had a powdery texture.
[0108] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and Triethyl Phosphite
[0109] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used is triethyl phosphite (CAS number: 122-52-1), which is from Fisher Scientific and is a commercially available organic phosphate containing three ethoxy groups. PEI is dissolved in a methanol solution, and then the phosphite is added in a ratio of 0.1 mol of phosphite per mol of N present in PEI, and stirred until uniform. Then, mesoporous alumina is dispersed in the mixture. After stirring for >4h, the solvent is removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite is controlled so that the PEI / phosphite mixture fills 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent has a powdery texture.
[0110] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and Triphenyl Phosphite
[0111] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used is triphenyl phosphite (CAS number: 101-02-0), which is from Fisher Scientific and is a commercially available organic phosphate containing three phenols. PEI is dissolved in a methanol solution, and then the phosphite is added in a ratio of 0.1 mol of phosphite per mol of N present in PEI, and stirred until uniform. Then, mesoporous alumina is dispersed in the mixture. After stirring for >4h, the solvent is removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite is controlled so that the PEI / phosphite mixture fills 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent has a powdery texture.
[0112] Example: Preparation of an Improved CO2 Adsorbent Containing Polyethyleneimine (PEI) and Trimethyl Phosphite
[0113] Branched polyethyleneimine (PEI), MW800 can be obtained from Sigma Aldrich. The phosphite compound used is trimethyl phosphite (CAS No. 121-45-9), which is a commercially available organic phosphate containing three methoxy groups. PEI is dissolved in a methanol solution, and then the phosphite is added in a ratio of 0.1 mol of phosphite per mol of N present in PEI, and stirred until uniform. Then, mesoporous alumina is dispersed in the mixture. After stirring for >4h, the solvent is removed using rotary evaporation and then dried in a vacuum oven at 100°C. The mass ratio of alumina and PEI / phosphite is controlled so that the PEI / phosphite mixture fills 40% to 80% of the mesopores of the mesoporous alumina. The resulting composite adsorbent has a powdery texture.
[0114] Example: Chemical characterization of improved CO2-philic phases and CO2 adsorbents
[0115] Chemical characterization was performed to confirm the nature of the modified CO2-philic phase. TGA combustion experiments were performed on the adsorbents containing the modified CO2-philic phase to characterize the total amount of organic matter present in the adsorbent and to confirm the presence of the incorporated phosphite molecules of the CO2-philic phase. The samples were heated to 900°C in dilute air and their mass loss was recorded. The total organic content was taken as the mass loss in this temperature interval after removing the contribution of CO2 and H2O lost at lower temperatures.
[0116] Example: TGA combustion experiment
[0117] Figure 4 and Figure 5 The mass loss and heat flow (DSC) curves of the material when exposed to diluted air and the temperature increased from room temperature to 900°C are shown. The figure shows that both the native PEI and PEI / phosphite adsorbents lost a lot of mass during the experiment because the organic components in the material were burned out under oxidative conditions. The mass loss of the adsorbent made with the phosphite additive was greater than the mass ratio of PEI to the carrier, which confirmed that the phosphite molecules have been incorporated into the CO2-philic phase. The DSC curve shows the different oxidation curves of the material during exposure, which also confirms that the phosphite molecules have been incorporated into the CO2-philic phase.
[0118] Example: CO2 adsorption process test
[0119] The adsorbents prepared with the modified CO2-philic phase were tested for CO2 adsorption in a TGA at 30°C and 400 ppm CO2 to simulate the gas contact step of the direct air capture process. The adsorbent was first treated in nitrogen at 100°C to desorb any bound H2O and CO2, and then equilibrated at 30°C under N2. The gas concentration was then isothermally switched to contain 400 ppm CO2 and equilibrated by N2, and the mass change was recorded. Under these anhydrous conditions, the mass increase of the material corresponds to the adsorption of CO2 and can therefore be used to measure the total amount of CO2 adsorbed on the material and the rate of adsorption.
[0120] The CO2 adsorption of various improved adsorbents was characterized using this approach and compared with the baseline PEI-based adsorbent.
[0121] Adsorbents are evaluated on two bases, i) CO2 capacity, i.e. millimoles of CO2 adsorbed per millimole of adsorbent present, and ii) amine efficiency, i.e. millimoles of CO2 adsorbed per millimole of N present. The former performance unit is used to show the overall performance of the adsorbent, the second performance unit is used to evaluate the performance of the amine polymer itself and takes into account the changes in the overall composition of the adsorbent.
[0122] Example: CO2 adsorption capacity of mesoporous alumina supported PEI and modified CO2-philic phase at 400 ppm CO2.
[0123] Figure 6 The transient mass change curve of the TGA CO adsorption experiment performed with the improved adsorbent containing PEI and phosphite additives supported on mesoporous alumina at 400 ppm CO (DAC conditions) is shown. The data of the adsorbent using PEI are also shown for reference. The data are reported in the form of amine efficiency (mmol CO2 / mmol N) to take into account the differences in amine loading of different adsorbents.
[0124] Figure 6The transient TGA absorption curves of adsorbents produced using PEI combined with a modified CO2-philic phase of a phosphite additive are compared to that of PEI under DAC conditions. Each adsorbent is able to adsorb CO2 under ultra-dilute conditions of 400 ppm, but with varying degrees of amine efficiency. Compared with PEI, the phosphite 4 additive appears to improve the overall adsorption performance of CO2, the CO2 adsorption performance of phosphites 2 and 3 is comparable to that of PEI, and the CO2 adsorption performance of phosphites 1 and phosphites 5 is lower than that of PEI. The initial adsorption rate follows the trend of PEI + phosphite 4 ≈ PEI + phosphite 2 > PEI + phosphite 3 ≈ PEII + phosphite 5 > PEI + phosphite 1 > PEI, so all phosphite additives appear to increase the initial adsorption rate of CO2 compared to PEI. This suggests that phosphite additives can increase the CO2 adsorption rate, allowing the adsorbent to reach equilibrium faster when adsorbing CO2 from air or other dilute streams. Without intending to be bound by theory, this unexpected result may be explained by the fact that the phosphite molecules create void spaces in the CO2-philic phase that allow unbound CO2 to diffuse more easily into the CO2-philic phase compared to PEI.
[0125] Example: Oxidative Stability Test
[0126] The oxidation stability of a material can be probed in a number of ways.
[0127] In this study, the oxidation stability of the adsorbents was evaluated by tracking the heat flow generated by the materials under isothermal oxidation conditions using DSC. In this paper, the adsorbents were first treated in an inert gas at 100°C to desorb any bound H2O and CO2, and then equilibrated in an inert gas at 125°C, 137.5°C, or 150°C for 60 minutes. The gas was then isothermally switched to a 17% O2 mixture or a 17% O2 and 20% CO2 mixture and maintained until the end of the reaction. This isothermal oxidation environment was maintained for a certain time to measure the heat flow and mass loss. To prevent further oxidation, the samples were then cooled to room temperature under N2. During these experiments, for each oxidation condition, the DSC measured the incremental heat flow, which increased, leveled off, and then decreased to zero. Oxidation was considered complete when the integrated heat flow change over 10 minutes was less than ±0.01% of the total integrated heat. To determine the change in the degree of oxidation over time, the loading of PEI was measured using the TGA burn-off method, and the DSC data was converted from the basic unit of mW / mg adsorbent to W / gPEI. According to the heat flow value when the DSC curve is close to the horizontal line, the offset is applied to drift correct the DSC data. The total heat is calculated by integrating the heat flow over time. The degree of oxidation of the DSC can be calculated by dividing the integrated heat flow curve by the total heat. The method has been pre-calibrated by the loss of amine efficiency as an in-situ method for tracking the rate of oxidative degradation chemical reactions, as shown in Figure 7. For more details on this method and its validation, please refer to the following papers: Nezam et al., ACS Sustainable Chem. Eng., 2021, 9, 8477-8486 and Racicot et al., J. Phys. Chem. C, 2022, 126, 8807-8816, which are incorporated herein by reference.
[0128] It is useful to evaluate the oxidative stability of a material in an environment containing both oxygen and CO2 because during the regeneration process, the desorbed CO2 is present in different concentrations and combined with the oxygen at elevated temperatures can affect the stability of the material. Alternatively, the oxidative stability of a material evaluated with oxygen (air) alone is a useful method for assessing the shelf life of a material when stored under ambient conditions.
[0129] Figure 8 The oxidation curves of CO2 adsorbents mixed with PEI and supported in mesoporous alumina with various phosphite additives in the presence of CO2 are shown. The figure shows two general categories of behavior: some phosphites slow down the oxidation of PEI, while some phosphites do not significantly change the oxidation rate of PEI. Specifically, phosphite 1, phosphite 2, phosphite 3, and phosphite 4 slow down the oxidation rate of PEI, while phosphite 5 has an oxidation rate comparable to that of PEI. Figure 8The differences in the extent of oxidation of different phosphites observed in the literature suggest that not all phosphites are effective antioxidants under the regenerative conditions of the CO2 capture process.
[0130] Fig. 9 The oxidation curves of CO adsorbents mixed with PEI and loaded in mesoporous alumina with multiple phosphite additives are shown in the presence of only air. The figure shows three general behavior categories: some phosphites slow down the oxidation of PEI, while some phosphites do not significantly change the oxidation rate of PEI, and some phosphites accelerate the oxidation of PEI. Specifically, phosphite 5 slows down the oxidation rate of PEI, while phosphite 2, phosphite 3, phosphite 4 and phosphite 7 accelerate the oxidation rate of PEI. Fig. 9 The differences in the extent of oxidation observed for different phosphites suggest that not all phosphites are effective antioxidants under conditions relevant for the storage of CO2 capture materials.
[0131] Figure 8 and Fig. 9 It is shown that phosphites are effective antioxidants when CO2 is present. It can also be seen that different phosphites are more advantageous in some applications than others, in which case different phosphites may help reduce oxidative degradation in some CO2 capture processes with high concentrations of CO2, as well as phosphites that help reduce oxidative degradation during storage of materials under ambient conditions. In this regard, the materials of the present disclosure can be adjusted according to their deployment process.
[0132] Example: Preparation of a honeycomb monolith with an improved CO2-philic phase containing polyethyleneimine (PEI) and tris(2,4-di-tert-butylphenyl) phosphite
[0133] To prepare the antioxidant adsorbent honeycomb monolith, tris(2,4-di-tert-butylphenyl) phosphite (phosphite 5) and PEI solutions were prepared: PEI was dissolved in toluene, and then tris(2,4-di-tert-butylphenyl) phosphite was added to the homogeneous solution at a ratio of 0.1 mol of phosphite per mol of N in PEI and stirred. The PEI / phosphite mixture was stirred at room temperature for about 1 hour and then impregnated into the honeycomb monolith.
[0134] A honeycomb monolith having a honeycomb channel structure composed of porous titanium dioxide is used.
[0135] The solution is then poured onto the honeycomb monolith in a controlled manner. The honeycomb monolith is soaked in the solution for 1.5 hours to fill the pore grid of the porous medium with the solution. When the PEI / phosphite solution completely occupies the pores, the solvent is removed. To remove excess solvent, an air knife is used to clean the channels of the honeycomb monolith, and then the honeycomb monolith is dried. The drying step is performed at 100°C under vacuum conditions for 10 hours. These drying conditions remove the solvent and exclude oxygen from the environment to prevent oxidation at high temperatures. The product honeycomb monolith contains 7wt% PEI and 11wt% tris(2,4-di-tert-butylphenyl) phosphite, with a pore filling rate of 68%. Fig.10 The TGA burnout curve of a honeycomb monolith prepared using PEI and phosphite 5 is shown.
[0136] It should be noted that the ratio, concentration, amount and other numerical data herein can be expressed in a range format. It should be understood that the use of this range format is for convenience and simplicity, and therefore, should be interpreted in a flexible manner, including not only the numerical values of the range limits clearly listed, but also all the individual numerical values or sub-ranges contained in the range, just as each numerical value and sub-range are clearly listed. For example, a concentration range of "about 0.1% to about 5%" should be interpreted as including not only the concentration of about 0.1wt% to about 5wt% clearly listed, but also a single concentration (e.g., 1%, 2%, 3% and 4%) and a sub-range (e.g., 0.5%, 1.1%, 2.2%, 3.3% and 4.4%) within the range. In one aspect, the term "about" can include traditional rounding according to the significant figures of the numerical value. In addition, the phrase "about 'x' to 'y'" includes "about 'x' to about 'y'".
[0137] Many changes and modifications may be made to the above aspects. All such modifications and variations are intended to be included within the scope of this disclosure and protected by the following claims.
Claims
1. An adsorbent comprising: A CO2-philic phase and a carrier, wherein the CO2-philic phase comprises a CO2-binding molecule portion and a phosphite-containing molecule, wherein the CO2-binding molecule comprises a CO2-binding portion.
2. The adsorbent according to claim 1, wherein the CO2-philic phase is an amine. The adsorbent according to claim 2 , wherein the amine is an amine polymer.
4. The adsorbent according to claim 3, wherein the amine polymer can be branched, hyperbranched, dendritic or linear.
5. The adsorbent according to claim 3, wherein the amine polymer is one of the following: polyethyleneimine, polypropyleneimine, polyallylamine, polyvinylamine, polyglycidylamine, or polystyrene-divinylbenzene polymer functionalized with amine or other amine polymers.
6. The adsorbent of claim 1, wherein the phosphite-containing molecule is a substituted phosphite, optionally wherein the substituted phosphite is a substituted aryl phosphite or a substituted phenyl phosphite.
7. The adsorbent according to claim 1, wherein the phosphite-containing molecule is selected from the group consisting of tris(2,4-di-tert-butylphenyl) phosphite, triphenyl phosphite, trimethyl phosphite, triethyl phosphite, diphenyl phosphite, tridodecyl trithiophosphite, trisnonylphenyl phosphite and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
8. The adsorbent of claim 2, wherein the amine is physically impregnated into the pores of the support.
9. The adsorbent according to claim 2, wherein the amine is physically impregnated into the surface of the support.
10. The adsorbent according to claim 2, wherein the amine is covalently bonded to the surface of the support.
11. The adsorbent according to claim 1, wherein the support is ceramic, metal, metal oxide, plastic, cellulose, carbon, zeolite, metal organic framework (MOF), porous organic framework (POF), covalent organic framework (COF), intrinsic microporous polymer (PIM), polymer, fibrous cellulose, glass fiber or boron nitride fiber. 12 . A contactor comprising a structure and the structure adsorbent according to claim 1 .
13. The contactor of claim 12, wherein the structure is selected from the group consisting of honeycomb, laminate, foam, fiber, minimal surface solid, powder disk, particle structure, or combinations thereof.
14. A system for capturing CO2 from a gas, optionally the gas being ambient air, the system comprising: a first device configured to introduce the gas into the adsorbent or contactor of any one of claims 1 to 13 to combine CO2 with the adsorbent; a second device configured to heat the sorbent containing bound CO2 to at least a first temperature to release the CO2; and A third device is configured to collect the released CO2.
15. The system of claim 14, wherein the sorbent is regenerated after heating to enable it to absorb CO2 from the gas.
16. The system of claim 14, wherein the adsorbent is in the form of honeycomb, laminate, fiber, foam, granules, powder disk, or a combination thereof.
17. The system of claim 16, wherein the open area of the cells is 0.3 to 0.
95.
18. The system of claim 14, wherein the gas approaches the honeycomb at a velocity of 0.25 m / s to 10 m / s.
19. The system of claim 14, wherein the system is configured to operate to remove CO2 from ambient air, wherein the ambient air has a low concentration of CO2.
20. A method for capturing CO2 from a gas, optionally the gas is ambient air, the method comprising: Introducing ambient air into the adsorbent or contactor of any one of claims 1 to 13 to combine CO2 with the adsorbent; heating the adsorbent to at least a first temperature to controllably release CO2; and The CO2 is collected in a CO2 collection device.
21. The method of claim 20, wherein heating the sorbent regenerates the sorbent so that it can absorb CO2 from ambient air.
22. The method of claim 20, wherein the adsorbent is heated by contact with steam.
23. The method of claim 20, wherein the method is configured to operate to remove CO2 from ambient air, wherein the ambient air has a low concentration of CO2.
24. The method of claim 20, wherein the adsorbent is in the form of a honeycomb, a laminate, a fiber, a foam, a granule, a powder disk, or a combination thereof.
25. A system for implementing the method of any one of claims 21 to 24.
Citation Information
Cited By
Impurity interference resistant low-concentration CO2 pressure swing adsorption purification process
CN121570941A
Low-concentration CO2 purification process resistant to impurities and interference
CN121570941B
